Leaching Kinetics of Iron Collector Containing PGMs - Evgeniy Kuzas; Ivan Sandalov; Aleksei Kritskii; Kirill Karimov (Metals)
The leaching kinetics of an industrial iron collector containing PGMs (Pd, Pt, Rh) in HCl and HF solutions were investigated. The effects of the HCl concentration (2.74–6.86 mol/L), the HF concentration (1.46–7.50 mol/L), temperature (323–363 K), and leaching time (0–210 min) on the extraction of Fe into the solution and Si into the gas phase from the iron collector were studied. The HCl concentration had a negative effect on the extraction of Si, which decreased from 78.2% to 58.1% and from 97.4% to 87.2% in the time ranges of 0–30 min and 30–120 min, respectively. This occurred due to the accumulation of Fe2+ in the solution and its interaction with HF, which led to a reduction in both the HF concentration and the extraction of Si. In addition, there were diffusion difficulties of the Fe and Si extraction because Fe precipitated on the surface of the cakes in the form of thin-film conglomerates of FeF2. This was confirmed by the XRF and EDS results, indicating that F was present on the surface of the cakes. The processes of the Fe and Si extraction were diffusion-chemically controlled and diffusion controlled—the apparent activation energies decreased from 26.9 kJ/mol to 7.8 kJ/mol and from 2.2 kJ/mol to 2.0 kJ/mol in the time range of 0–120 min, respectively. Using the shrinking core model and the full factorial experiment model, the kinetic equations, the optimal parameters of iron collector leaching, and the extraction rates of Fe and Si were determined. These optimal parameters ensure the extraction of Fe and Si at the level of 95% with high leaching rates: the HCl concentration of 4.36 mol/L, the HF concentration of 6.93 mol/L, temperature of 363 K, and leaching time of 80 min.